(untitled) (International Journal of Engineering and Computer Science, 2018)
A mobile ad-hoc network (MANET) infrastructure less dynamic network consists of collection of wireless mobile node that communicates with each other without the use of centralized network. Security in MANET is the most important concern for the basic functionality of network. The malicious node falsely advertises the shortest path to the destination node during the route discovery process by forging the sequence number and hop count of routing message . In this paper ,To avoid and remove this effect we will used Digital Signature Techniques